2020
DOI: 10.1001/jamanetworkopen.2019.21647
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Death From Unintentional Injury Among Patients With Cancer in the United States

Abstract: IMPORTANCE Previous studies have suggested that patients with cancer may be at an increased risk of death from unintentional injury, but to our knowledge, no large studies have examined the rates of death from unintentional injury among patients with cancer. OBJECTIVE To characterize the incidence of death from unintentional injury among patients with cancer in the United States. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study included patients diagnosed with a first primary cancer between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 42 publications
5
55
1
Order By: Relevance
“…The mortality rates of fatal infections were calculated as the number of deaths from infections divided by person-years of follow-up, whereas the SMRs and corresponding 95% confidence intervals (CIs) of non-cancer deaths were calculated based on previously published protocols [16][17][18][19]. The SMRs were estimated as the ratios of observed to expected number of deaths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality rates of fatal infections were calculated as the number of deaths from infections divided by person-years of follow-up, whereas the SMRs and corresponding 95% confidence intervals (CIs) of non-cancer deaths were calculated based on previously published protocols [16][17][18][19]. The SMRs were estimated as the ratios of observed to expected number of deaths.…”
Section: Resultsmentioning
confidence: 99%
“…1 show the SMRs of infectious mortality by time since cancer diagnosis. With all cancer types combined, the SMR of deaths from infectious diseases was high within 1 year after cancer diagnosis (SMR, 5.09; 95% CI 5.04-5.14), decreased in the first 5 years after diagnosis, rose gradually since 5 years after diagnosis, and reached a peak after [ 19). In various types of cancer, three patterns were observed in the risk of dying from infectious diseases with follow-up time.…”
Section: Fatal Infections By Major Causes and Anatomic Sitesmentioning
confidence: 99%
“…First, there is a risk of reporting bias in death certificates which could lead to misclassification of causes of death [ 53 , 54 ]. However, the SEER mortality data were provided by the NCHS (National Center for Health Statistics) and NVSS (National Vital Statistics System) and systematic and standardized data collection procedures are used to ensure that the causes of death recorded in SEER are accurate [ 55 ]. Further, previous studies have also examined the validity and reliability of the use of death certificates recorded in the SEER and the results suggested that they were acceptable [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we were not able to analyze the cause and effect relationship between different risk factors and distinct causes of death. Nevertheless, analyzing the extensive amount of data available from the SEER database remains a powerful, useful, and integral tool in medical research for the purpose of exploratory analyses [ 55 ]. Third, we were unable to obtain data on genetic information (such as MMR (defective mismatch repair) genes or mutations status of KRAS and BRAF) and dietary habits, which prohibited us from taking these features into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation